2020
DOI: 10.1002/cbin.11298
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG1 exerts a protective role in cardiomyocytes hypertrophy via targeting miR‐15a‐5p/HMGA1 axis

Abstract: Heart failure preceded by pathological cardiac hypertrophy is a leading cause of death. Long noncoding RNA small nucleolar RNA host gene 1 (SNHG1) was reported to inhibit cardiomyocytes apoptosis, but the role and underlying mechanism of SNHG1 in pathological cardiac hypertrophy have not yet been understood. This study was designed to investigate the role and molecular mechanism of SNHG1 in regulating cardiac hypertrophy. We found that SNHG1 was upregulated during cardiac hypertrophy both in vivo (transverse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…While lncRNA mimics have been used to express specific oligonucleotides , lncRNA-Plscr4 overexpression regulates mitochondrial function to attenuate hypertrophic stress by targeting miR-214 in mice-TAC or Ang-II-treated CMs (Lv et al, 2018;Zhang M. et al, 2019). Additionally, silencing of lncRNA-Uc.323 or overexpression of lncRNA-Ahit could attenuate phenylephrine-induced CM enlargement through the mitochondrial pathway (Liu et al, 2016;Viereck et al, 2016;Yan et al, 2019;Sun et al, 2020).…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…While lncRNA mimics have been used to express specific oligonucleotides , lncRNA-Plscr4 overexpression regulates mitochondrial function to attenuate hypertrophic stress by targeting miR-214 in mice-TAC or Ang-II-treated CMs (Lv et al, 2018;Zhang M. et al, 2019). Additionally, silencing of lncRNA-Uc.323 or overexpression of lncRNA-Ahit could attenuate phenylephrine-induced CM enlargement through the mitochondrial pathway (Liu et al, 2016;Viereck et al, 2016;Yan et al, 2019;Sun et al, 2020).…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…The lncR‐UCA1 is upregulated in mice hypertrophic cardiomyocytes, and it can sponge miR‐184, enhancing the expression of HOXA9 114 . A detailed report on lncRNAs in cardiac hypertrophy is reported in the work by Liu and colleagues, 115 which also implicates the lncRNAs MHRT, 116 Meg3, 117 DACH1, 118 H19, 119 Plscr4, 120 SNHG1, 121 TINCR, 122 Uc.323, 123 and Ahit 124 . Other lncRNAs have also been implicated in heart failure, 111 as does the heart‐related circRNA (HRCR), which in mice was found to acts as endogenous sponge to mir‐223, protecting them from hypertrophic stimuli 125 .…”
Section: Lncrnas In Obesity‐associated Diseasesmentioning
confidence: 95%
“…Indeed, current therapies for CVD such as cardiac hypertrophy currently alleviates symptoms, but new genetic analyses could provide new therapeutic targets 115 . Modulation of lncRNAs such as Meg3, Plscr4, H19, SNHG1, uc.323, or Ahit could attenuate the increasing size of cardiomyocytes 117,119–121,123,124 . Moreover, a specific class of antisense oligonucleotides, GapmeRs, shows great promise in pharmacological silencing of lncRNAs in vivo, 170 and even if no clinical trial has been performed, therapeutic GapmeR injections have been found to modulate lncRNAs such as Chast 171 and Meg3 172 in animal models of pressure overload or Wisper in myocardial infarction 108,173 .…”
Section: Lncrnas In Obesity‐associated Diseasesmentioning
confidence: 99%
“…33,56,58 Overexpression of Lnc-H19, Lnc-SNHG1, Lnc-uc.323 or loss-expression of Lnc-Ahit and Lnc-Chast could reduce the cardiomyocytes size in response to phenylephrine. 36,47,59,60 Conditional knockout of Lnc-DACH or overexpression Lnc-TINCR resulted in increasing calcium transient, and improving cardiac function after transverse aortic constriction in mice. 41 Inhibition of Lnc-Chaer expression before the onset of pressure overload substantially attenuates cardiac hypertrophy on mouse model.…”
Section: Ln Crna : a P Otential Targ E T For C Ardiac Hypertrophymentioning
confidence: 99%
“…Silenced Lnc‐MEG3 or overexpression Lnc‐Plscr4 and Lnc‐CHAR could attenuate the increasing size of cardiomyocytes induced by angiotensin II (Ang‐II) 33,56,58 . Overexpression of Lnc‐H19, Lnc‐SNHG1, Lnc‐uc.323 or loss‐expression of Lnc‐Ahit and Lnc‐Chast could reduce the cardiomyocytes size in response to phenylephrine 36,47,59,60 . Conditional knockout of Lnc‐DACH or overexpression Lnc‐TINCR resulted in increasing calcium transient, and improving cardiac function after transverse aortic constriction in mice 41 .…”
Section: Lncrna: a Potential Target For Cardiac Hypertrophymentioning
confidence: 99%